Factors associated with elevated gentamicin trough levels in neonates: a retrospective analysis of dosing and clinical parameters - Trah, Julian; Deindl, Philipp; Luister, Alexandra; Langebrake, Claudia; Singer, Dominique; Ebenebe, Chinedu Ulrich (Frontiers in Pediatrics, 2025)
ObjectiveInvestigate determinants of elevated gentamicin trough levels in neonates.MethodsThis single-center retrospective analysis used a multivariate linear regression model to explore the relationship between gentamicin trough concentrations and factors such as creatinine levels, dosage, day of life, sex, CRP levels, and dosing interval in neonates.ResultsIn 215 neonates, including 68 (31.6%) premature neonates with a postmenstrual age of ≤35 weeks, shorter dosing intervals, higher creatinine levels, and increased dosage were linked to higher gentamicin trough levels. Elevated CRP levels corresponded with lower trough levels.ConclusionThis study highlights the critical role of dosing frequency, kidney function, and inflammatory status in influencing gentamicin trough levels in neonates. However, all gentamicin trough levels were within the 2 µg/ml threshold.